Prevalence of Helicobacter pylori in Non-Cardia Gastric Cancer in China: A Systematic Review and Meta-Analysis - Lu, Yong; Xiao, Fei; Wang, Yuan; Wang, Zhenyu; Liu, Di; Hong, Feng (Frontiers in Oncology, 2022)
Abstract Non-cardia gastric cancer was significantly associated with Helicobacter pylori (H. pylori) infection. Reducing H. pylori prevalence was an important prevention strategy for non-cardia gastric cancer. However, national level data on the H. pylori prevalence in non-cardia gastric cancer were limited in China. Therefore, we conducted this study to estimate the pooled prevalence of H. pylori in non-cardia gastric cancer in China. We searched PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang, and VIP Database for Chinese Technical Periodicals for studies reporting H. pylori prevalence in non-cardia gastric cancer in China which were published before Sept 1, 2021. Pooled prevalence was calculated using a random-effect model. Subgroup analysis and meta-regression were used to explore the potential sources of heterogeneity. Egger’s test and funnel plot were used to assess publication bias. A total number of 55 studies with 5,324 cases of non-cardia gastric cancer were included in this study. The pooled prevalence of H. pylori in non-cardia gastric cancer in China was 66.5% (95%CI: 62.0%-71.0%, I2=93.8%, P<0.0001). In subgroup analysis, significant difference for the prevalence of H. pylori in non-cardia gastric cancer was noted when stratified by geographic region of China (P=0.0112). The highest H. pylori prevalence (78.9%, 95%CI: 69.9%-87.8%) was noted in Northwest China and the lowest (53.1%, 95%CI: 38.9%-67.3%) was in North China. In meta-regression, the significant association between H. pylori prevalence and geographic region was found, while type of sample, H. pylori testing method, diagnosis period, detection timing, type of study design, quality grade, publication year, and sample size were not associated with the prevalence of H. pylori in non-cardia gastric cancer (P>0.05). A large proportion of non-cardia gastric cancers were associated with H. pylori infection in China, emphasizing the possible benefits of H. pylori eradication for the prevention and control of non-cardia gastric cancer.